Удивительные сказки малышам: сказки / худож. В. Нечитайло - Нечитайло В. (Любимые сказки малышам, 2010)
Экземпляры: аб. ДБ (2017.20.12) / Инвентарный номер: 3837 / Цена: / Сис.шифр: 84(0) / Авт.знак: У 30 / ГРНТИ: 17 / ББК: 84(0)